The effectiveness strategy of stakeholder engagement approach in construction industry - Siti Fairuz , Kamsar (2014)
Effectiveness of stakeholder engagement is one of important determinants to success of completion of project in construction industry. It is because effectiveness of stakeholder engagement will influence the project performance in construction industry. When the companies have effectiveness of stakeholder engagement and efficiently stakeholder engagement it can help the company to increase their effectiveness performance of the project from aspect cost, time and quality. The purpose of this research is to determine the effectiveness of stakeholder engagement approach and their performance in construction industry. These researches also identify the benefit and challenges during managing stakeholder. In conducting this study, questionnaire was distributed to respondent by email and face to face. Questionnaire was distributed to respondent who are developer under member CIDB in Kuantan, Pahang areas. From 75 questionnaires distribute, only 63 were collected back. The data solicited were than analyzed by using SPSS software to get result. In conclusion, effectiveness of stakeholder engagement approach is the important to get the project success or failure. Once stakeholder engagement approach is effective in construction industry, then it will improve the project performance in construction project